Maize Source Leaf Adaptation to Nitrogen Deficiency Affects Not Only Nitrogen and Carbon Metabolism But Also Control of Phosphate Homeostasis - Schlüter, Urte; Mascher, Martin; Colmsee, Christian; Scholz, Uwe; Braeutigam, Andrea; Fahnenstich, Holger; Sonnewald, Uwe (Plant Physiology, 2012)
Crop plant development is strongly dependent on the availability of nitrogen (N) in the soil and the efficiency of N utilization for biomass production and yield. However, knowledge about molecular responses to N deprivation derives mainly from the study of model species. In this article, the metabolic adaptation of source leaves to low N was analyzed in maize (Zea mays) seedlings by parallel measurements of transcriptome and metabolome profiling. Inbred lines A188 and B73 were cultivated under sufficient (15 mM) or limiting (0.15 mM) nitrate supply for up to 30 d. Limited availability of N caused strong shifts in the metabolite profile of leaves. The transcriptome was less affected by the N stress but showed strong genotype-and age-dependent patterns. N starvation initiated the selective down-regulation of processes involved in nitrate reduction and amino acid assimilation; ammonium assimilation-related transcripts, on the other hand, were not influenced. Carbon assimilation-related transcripts were characterized by high transcriptional coordination and general down-regulation under low-N conditions. N deprivation caused a slight accumulation of starch but also directed increased amounts of carbohydrates into the cell wall and secondary metabolites. The decrease in N availability also resulted in accumulation of phosphate and strong down-regulation of genes usually involved in phosphate starvation response, underlining the great importance of phosphate homeostasis control under stress conditions.